2023
DOI: 10.1021/acs.nanolett.3c00114
|View full text |Cite
|
Sign up to set email alerts
|

Atom-by-Atom Direct Writing

Abstract: Direct-write processes enable the alteration or deposition of materials in a continuous, directable, sequential fashion. In this work, we demonstrate an electron beam direct-write process in an aberration-corrected scanning transmission electron microscope. This process has several fundamental differences from conventional electron-beam-induced deposition techniques, where the electron beam dissociates precursor gases into chemically reactive products that bond to a substrate. Here, we use elemental tin (Sn) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…It has recently been shown that Sn atoms can be directly written into single‐layer graphene using the e‐beam. [ 50 ] This suggests that patterning in a similar manner to what has been shown here should be possible in single‐layer graphene as well, if global conditions of the sample can be discovered or predicted, which will facilitate a simultaneous, global, bottom‐up process that can complement the top‐down patterning.…”
Section: Discussionmentioning
confidence: 64%
“…It has recently been shown that Sn atoms can be directly written into single‐layer graphene using the e‐beam. [ 50 ] This suggests that patterning in a similar manner to what has been shown here should be possible in single‐layer graphene as well, if global conditions of the sample can be discovered or predicted, which will facilitate a simultaneous, global, bottom‐up process that can complement the top‐down patterning.…”
Section: Discussionmentioning
confidence: 64%
“…[2][3][4][5] Numerous demonstrations have ranged from the creation of nanowires [6,7] to 1D chains of atoms, [8][9][10][11][12] sculpting, [13][14][15][16][17] molecule-by-molecule deposition, [18] the movement of single atoms, [19][20][21][22][23] the attachment of atoms, [24][25][26][27][28] and atomic patterning [29] and writing. [30] At the same time, feedback-controlled methods for material transformation, manipulation, and beam control in a STEM have also become increasingly refined, now leveraging artificial-intelligence (AI) based decision making. [31][32][33][34][35][36][37][38] Likewise, advances in bottom-up synthesis techniques have shown an impressive ability to tailor molecular structures with atomic precision, revealing junction states, spin centers, quantum spin chains, topologically induced energy bands, and spin splitting.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this differs from STEM-based EBID [18,51] in that it is not confined to the dissociation of a precursor gas but also includes working with purified precursor materials. [29,30] This would enable multi-component synthesis processes combined with atomic-scale tailoring, real-time feedback control, and AI decision making.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations